Processes underlying unintentional finger-force changes in the absence of visual feedback - Ambike, Satyajit; Zatsiorsky, Vladimir M.; Latash, Mark L. (Experimental brain research, 2015)
Previous reports show that the forces produced by the fingers of one hand drop exponentially over time in the absence of visual feedback on the forces. We study the force production by the index fingers of both hands with no visual feedback. Subjects produced a specified total force with a specific contribution from each finger by pressing on force sensors. We observed that in the absence of visual feedback: (1) The finger forces dropped with time by an amount proportional to the magnitude of the initial force. For low initial force values (<7 % of MVC of individual finger force), the finger forces showed an increase; (2) the total force (sum of finger forces) evolution showed similar features; (3) finger forces changed in a way that facilitated more equitable force production by the two fingers; (4) all the force–time changes resemble exponential functions with similar time constants (~15 s). We propose that two processes interact to produce these patterns. (1) RC back - coupling : The central nervous system defines referent coordinates (RCs) for the digit tips, and the difference between the referent and actual coordinates leads to force production. If actual coordinates are not allowed to move to referent ones, referent coordinates show a slow drift toward the actual ones, leading to a force drop. (2) Sensory adaptation : This process, possibly related to sensory receptor characteristics, leads to an increase in finger force. RC back-coupling provides a common account of this and other reported phenomena of hand force or position changes across transient, external perturbations.